Abnormal Uterine Bleeding- evaluation by Endometrial Aspiration - Pratibha Singh (Wolters Kluwer Medknow Publications, 2018)
Endometrial evaluation is generally indicated in cases presenting with abnormal uterine bleeding (AUB), especially in women more than 35 years of age. AUB encompasses a variety of presentation, for example, heavy menstrual bleeding, frequent bleeding, irregular vaginal bleeding, postcoital and postmenopausal bleeding to name a few. Many methods are used for the evaluation of such cases, with most common being sonography and endometrial biopsy with very few cases requiring more invasive approach like hysteroscopy. Endometrial aspiration is a simple and safe office procedure used for this purpose. Materials and Methods: We retrospectively analyzed cases of AUB where endometrial aspiration with Pipette (Medgyn) was done in outpatient department between January 2015 and April 2016. Case records (both paper and electronic) were used to retrieve data. Results: One hundred and fifteen cases were included in the study after applying inclusion and exclusion criteria. Most cases were between 46 and 50 years of age followed by 41-45 years. No cases were below 25 or more than 65 years of age. Heavy menstrual bleeding was the most common presentation of AUB. Adequate samples were obtained in 86% of cases while 13.9% of cases' sample was inadequate for opinion, many of which were later underwent hysteroscopy and/or dilatation and curettage (D and C) in operation theater; atrophic endometrium was the most common cause for inadequate sample. Uterine malignancy was diagnosed in three cases. Discussion: Endometrial aspiration has been compared with traditional D and C as well as postoperative histopathology in various studies with good results. Many such studies are done in India as well as in western countries confirming good correlation with histopathology and adequate tissue sample for the pathologist to give a confident diagnosis. No complication or side effect was noted with the use of this device. Conclusion: Endometrial aspiration is a simple, safe, and effective method to sample endometrium in cases of AUB avoiding risk of anesthesia and is less time-consuming. Many similar devices are also available in the market and need to be popularized in all parts of the country.